1991
DOI: 10.1111/j.1432-1033.1991.tb16188.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of ribosomal subunits

Abstract: A yeast ribosomal subunit association factor (AF) has been purified from a high-salt ribosomal wash. The purified enzyme is a thermostable protein that associates ribosomal subunits at low Mg2 + concentration without requiring energy. It appears to be an aggregate of trimers or dimers (molecular mass 125 or 79 kDa) which on sodium dodecyl sulfate gels shows the presence of a major protein band whose estimated molecular mass is 43 kDa. Evidence also indicates the existence of a 50-kDa polypeptide which seems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…EF1␣, which was present in one CF I preparation (14), was not added in our reconstitution studies, but may be present in the CF II or PF I fractions that were used for reconstitution. However, given the lack of any evidence to date implicating this protein in mRNA processing, its cytoplasmic localization (28), and large abundance (29), this protein was probably a contaminant in the CF IA fraction and not a true component of CF IA.…”
Section: Discussionmentioning
confidence: 99%
“…EF1␣, which was present in one CF I preparation (14), was not added in our reconstitution studies, but may be present in the CF II or PF I fractions that were used for reconstitution. However, given the lack of any evidence to date implicating this protein in mRNA processing, its cytoplasmic localization (28), and large abundance (29), this protein was probably a contaminant in the CF IA fraction and not a true component of CF IA.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier report from our laboratory suggested that AF was related to the elongation factor EF-1α (Herrera et al 1991). However, using purified antiserum against EF-1α, it was determined that AF does not cross react with the antibody to EF-1α (data not shown).…”
Section: Resultsmentioning
confidence: 79%
“…Cells were homogeneized according to (Herrera et al 1991) and polysomes, prepared following the method previously reported (Gallis et al 1975), were treated with 0.5 M KCl to obtain the ribosomal pellet and the high salt ribosomal wash (Herrera et al 1991).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations